حرية الصحافة الإلكترونية في سوريا: دراسة تحليلية مقارنة بين القانون والشريعة: FREEDOM OF ELECTRONIC PRESS IN SYRIA: ANALYTICAL AND COMPARATIVE STUDY BETWEEN THE LAW AND SHARIAH - AL ZUABI, LORANS HASSAN; Abdul Shukor, Syahirah; Ali Abdul Rab, Muneer; Nik Salleh, Nik Salida Suhaila (Malaysian Journal of Syariah and Law, 2021)
Abstract in English: This study addresses the press’s issue as one of the aspects of freedom of opinion and expression. Then, it focused on the reality of electronic journalism in Syria, based on its significance and spreading and keeping pace with technology. The researcher took Syrian law as a model for the study, and among the reasons that prompted him to do so was the scope and significance of the problem that was manifested in the legislator’s failure to deal with e-journalism, and to create modern laws that take Islamic law into account in their provisions, in line with the practises of that press. In addition, some articles of media laws and legislations remain ambiguous without clarification, which caused confusion and disparity between the freedom of the electronic press and practices. The importance of this study stems from the attempt to address the scarcity of previous studies that dealt with the issue of electronic press freedom in Syria and their mistreatment of a number of essential aspects that must be highlighted, such as the factors which limit the freedom of press. The purpose of this study is to present the reality of electronic journalism in Syria, and to show both negative and positive effect of laws on its expression, as well as to highlight cases of its validity in Islam, while at the same time demonstrating the compatibility of Syrian law provisions with it. In order to support the objectives of the study, the researcher adopted descriptive method of analysis. The study summarised a number of conclusions, including the limitation of the freedom of the electronic press in Syria, as a result of the vagueness of the laws that govern them, as well as the lack of a special law for them, and the failure to comply with Islamic legislation in enforcing some of its provisions. Abstract in Arabic: تناولت هذه الدراسة موضوع حرية الصحافة، باعتبارها أحد أوجه حرية الرأي والتعبير، حيث ركزت في مضمونها، على واقع حرية الصحافة الإلكترونية ، وذلك انطلاقاً من أهميتها، وسرعة انتشارها، ومواكبتها للتطور والتكنولوجيا. وقد حدد الباحث القانون السوري نموذجاً للدراسة، ومن الأسباب التي دفعته لذلك، عمق و أهمية المشكلة، والتي تجلت في تقصير الـمُشرِّع في تناول الصحافة الإلكترونية، وعدم وضع قوانين حديثة، تراعي التشريع الإسلامي في أحكامها، لتتناسب مع ممارسات هذه الصحافة، فضلاً عن بقاء بعض القوانين المتعلقة بها مبهمة، مما أدى إلى الخلط وعدم التوازن بين حرية الصحافة الإلكترونية وممارستها. وتأتي أهمية هذه الدراسة، في محاولة المساهمة في معالجة نُدرة الدراسات السابقة التي تناولت موضوع حرية الصحافة الإلكترونية في سوريا وإغفالها لعدد من الجوانب المهمة الواجب توفرها، مثل والعوامل المقيدة لحرية الصحافة، و تهدف الدراسة، إلى عرض واقع الصحافة الإلكترونية في سوريا، وبيان مدى تأثير القوانين على حريتها سلباً وإيجاباً، إضافة إلى إبراز حالات مشروعيتها في الإسلام، مع بيان توافق أحكام القانون السوري معها. وقد اتبع الباحث لخدمة أهداف الدراسة، منهج التحليل الوصفي. وخلصت الدراسة لعدد من النتائج، منها تقيد حرية الصحافة الإلكترونية في سوريا، نتيجة إبهام القوانين التي تنظمها، إضافة إلى عدم وجود قانون خاص بها، وعدم مراعاة التشريع الإسلامي في تطبيق بعض أحكامها.